2019
DOI: 10.1080/10888705.2019.1571921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calf Horn as Chews on the Behavior of Laboratory Dogs

Abstract: It is increasingly required that non-human animals in laboratories are provided with adequate enrichment to promote the welfare of the animals. In a previous publication we showed that laboratory dogs intensively used the horn of calf hooves as chewing objects. In this report, we describe the effect of calf horn on selected behaviors of 62 laboratory dogs (60 beagles, two Foxhound crossbreds) in three research facilities (A, B, C). In addition, we assessed the dogs' tooth condition and fecal consistency. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Besides the positive effects on oral health, chewing agents can also affect animal behavior. A recent study reported that the use of calf horn as a chewing agent increased exploratory behavior and decreased inactivity behavior in laboratory dogs ( Ketter et al, 2020 ). Although evaluation of dog behavior was beyond the scope of this study, future work may consider the impact of bovine bones on dog behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the positive effects on oral health, chewing agents can also affect animal behavior. A recent study reported that the use of calf horn as a chewing agent increased exploratory behavior and decreased inactivity behavior in laboratory dogs ( Ketter et al, 2020 ). Although evaluation of dog behavior was beyond the scope of this study, future work may consider the impact of bovine bones on dog behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The feeding pattern of domestic dogs can be considered the ecologically relevant form of the domestic dog's feeding behaviour, and the feeding method used for domestic dogs is far from fulfilling behavioural needs. 11 In the guidelines for husbandry and care of laboratory dogs, 25 chewing has been considered a rewarding experience and it has been recommended to be activities in the pen environment, 26 together with cardboard boxes stuffed with shredded paper bedding and dog treats, softwood, rawhide or nylon chews.…”
Section: Discussionmentioning
confidence: 99%
“…In the guidelines for husbandry and care of laboratory dogs, 25 chewing has been considered a rewarding experience and it has been recommended to be activities in the pen environment, 26 together with cardboard boxes stuffed with shredded paper bedding and dog treats, softwood, rawhide or nylon chews.…”
Section: Discussionmentioning
confidence: 99%
“…Kennelled dogs provided with enrichment feeders have increased activity and explorative behaviours. 14,15 Increasing activity is potentially beneficial given that inactivity in kennelled dogs is associated with depression, boredom and a reduced quality of life (QOL). 16,17 Providing dogs in boarding kennels with 20 minutes a day to use puzzle feeders was associated with a reduction in stress-related behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research involving enrichment feeding in companion animals has involved kennelled dogs or cats. Kennelled dogs provided with enrichment feeders have increased activity and explorative behaviours 14,15 . Increasing activity is potentially beneficial given that inactivity in kennelled dogs is associated with depression, boredom and a reduced quality of life (QOL) 16,17 .…”
Section: Introductionmentioning
confidence: 99%